IMPLEMENTASI PERSONALIZED LEARNING MENGGUNAKAN LITERCY ICT DIGITAL : SEBUAH SYSTEMATIC LITERATUR REVIEW - winarno, Winarno (FKIP Universitas Citra Bangsa, 2024)
Abstract. The different learning needs of students are met by accommodating and personalizing their education. Technology is often used to facilitate the personalization of student learning environments. However, the educational world is currently struggling to implement such an approach. The change in digital literacy practices in the context of education requires a continuous re-examination of the conceptualization of digital literature education. The research uses the method of systematic literature review (SLR) to trace selected literature from 35 Scopus indexed journals on the implementation of personalized learning using digital ICT literacy. The results of the research show that the urgent need of students for personalized learning becomes more evident as educational information progresses. Personalized Recommendation Technology (PR) can help personalized learning and improve student learning efficiency. The development of personalized learning platforms can be done based on CF (collaborative filtering) algorithms, and perform system needs analysis. But it still requires an evaluation of personalized learning features in order to be able to understand the behavioral features of learning intelligently. Abstrak. Kebutuhan pembelajaran yang berbeda dari siswa dipenuhi dengan mengakomodasi dan mempersonalisasi pendidikan mereka. Teknologi sering digunakan untuk memfasilitasi personalisasi lingkungan belajar siswa. Namun, saat ini dunia pendidikan mengalami kesulitan untuk menerapkan pendekatan tersebut. Perubahan praktik literasi digital dalam konteks pendidikan mengharuskan terus meninjau kembali konseptualisasi pendidikan literasi digital. Penelitian ini menggunakan metode systematic literature review (SLR) untuk menelusuri literatur-literatur terpilih dari 35 jurnal terindeks Scopus tentang implementasi pembelajaran dipersonalisasi menggunakan litercy ICT digital. Hasil penelitian menunjukan kebutuhan mendesak pelajar akan pembelajaran yang dipersonalisasi menjadi lebih jelas seiring dengan kemajuan informasi pendidikan. Teknologi rekomendasi yang dipersonalisasi (PR) dapat membantu pembelajaran yang dipersonalisasi dan meningkatkan efisiensi pembelajaran peserta didik. Pengembangan platform pembelajaran yang dipersonalisasi dapat dilakukan berdasarkan algoritma CF (collaborative filtering), dan melakukan analisis kebutuhan sistem. Tetapi tetap perlu adanya evaluasi fitur pembelajaran yang dipersonalisasi agar dapat memahami fitur perilaku belajar secara cerdas.